Synthesis and Characterization of Green Zinc Oxide Nanoparticles with Antiproliferative Effects through Apoptosis Induction and MicroRNA Modulation in Breast Cancer Cells - Amir Hossein Aalami; Mohammad Mesgari; Amirhossein Sahebkar (Bioinorganic Chemistry and Applications)
Changes in the expression of microRNAs can affect cancer cells’ viability and behavior and the impact on cancer treatment. In this study, the expression of miR-155-5p, miR-203a-3p, and miR-223-3p in the MCF7 cancer cell line was studied when exposed to ZnO nanoparticles synthesized through a green route. Mentioned ZnO-NPs were well characterized by UV-vis spectroscopy, DLS, XRD, FTIR, FE-SEM, EDX, zeta potential, and AFM analyses. Cellular studies were conducted using ZnO-NPs before miRNA investigations including MTT cytotoxicity test against MCF7, MDA-MB-231, and HFF cell lines. Moreover, apoptosis assays were performed using morphological analysis, fluorescent dyes, flow cytometry, and evaluation of caspase-3 and caspase-8 gene expression. Biological properties such as the antioxidant and antimicrobial activity of these novel ZnO-NPs were considered. MTT assays showed that the inhibitory concentration (IC50) of ZnO-NPs after 24 h was 11.16 μg/mL, 60.08 μg/mL, and 26.3 μg/mL on MCF7, MDA-MB-231, and HFF cells, respectively. The qRT-PCR results showed reduced expression of miR-155-5p, miR-203a-3p, and miR-223-3p when the MCF7 cells were treated with the IC50 concentration of ZnO-NPs (11.16 μg/mL). The antioxidant activity results showed EC50 values at 57.19 μg/mL and 31.5 μg/mL in DPPH and ABTS assays, respectively. The antimicrobial activity of ZnO-NPs was determined on Gram-negative and Gram-positive bacterial strains and fungi using MIC and MBC assays. These NPs had a significant effect in reducing the expression of microRNAs in breast cancer cells. Finally, ZnO-NPs exerted antioxidant and antimicrobial activities.